Analysis of acquisition and the monthly cost of antihypertensive therapy with modern fixed-dose combinations in the Far Eastern Federal District - M. S. Soboleva; E. E. Loskutova (Фармакоэкономика, 2021)
Objective: analyzing the acquisition and monthly costs for patients on modern fixed-dose antihypertensive combinations in three regions of the Far Eastern Federal District.Material and methods. Intra-group analysis of retail of antihypertensive drugs for 2019 in drugstores of the Khabarovsk Region, Sakhalin Region, Amur Region (n=100) was carried out. The calculation of the monthly cost of therapy was performed and total sales indicators were identified. Statistical analysis: dispersion analysis, Spearman's rank correlation coefficient, Kruskal–Wallis test.Results. The maximum demand in patients among combinations of -blockers in the price range of 100-500 rubles: atenolol+chlortalidone; bisoprolol+amlodipine. In the grope of combinations of angiotensin-converting enzyme inhibitors with diuretics/calcium channel blockers, the most often acquired were: perindopril/ramipril+indapamide/amlodipine, enalapril+hydrochlorothiazide – in the price segment of 500–1000 rubles. Preferences for the use of combinations of angiotensin II receptor blockers+diuretic/calcium channel blockers: valsartan+amlodipine with a monthly cost of therapy of 300–500 rubles; losartan+hydrochlorothiazide – 100–500 rubles and azilsartan+chlortalidonee – 500–1000 rubles. The most popular three-component drugs were valsartan+amlodipine+hydrochlorothiazide, perindopril+amlodipine+indapamide with a monthly cost over 500 rubles. Differences in the acquisition structure of fixed-dose antihypertensive combinations between regions were statistically significant.Conclusion. The share of sales of combined antihypertensive drugs remains insignificant. The main selection criteria within an international nonproprietary name are affordability or trust in a brand. The presence of a reliable correlation of the acquisition structure with the region proves the influence of regional preferences of specialists in drug prescribing.